The Political Economy of Village Level Theocracies in the Ìlàjẹ Coastline, Southwest Nigeria - Babajide Ololajulo (Yoruba Studies Review)
In 1947, a group of fishermen from the coastal area of Ìlàjẹ, Ondo State, Nigeria who were members of the Aládúrà, an independent Church movement in southwest of Nigeria, came together to establish a theocratic settlement, which they named Ayétòrò. A few years after, other theocratic settlements emerged in quick succession and by 1980 there were more than fifty such villages along the Ìlàjẹ coastline. The pertinent question is why this form of community organization is pervasive among the Ìlàjẹ. The main argument of this article, following ethnographic data collected from four theocratic settlements, which are regarded as the core village theocracies, is that a flexible land tenure regime and a loose traditional political system, among other factors of environment and kinship structure, ensured easy access to land and served to authenticate the spiritual leadership claims of founders of theocratic settlements. The conclusion reflects on the future of theocratic settlements against the background of increasing modernization along the Ìlàjẹ coastline.